A Value-Oriented Method of Arabic Language Education: Interpreting “Labanan Khalishan” as a Medium for Enhancing Semantic Understanding and Moral Character - Rahmatullah, Muhammad Ali Jum’ah; Nasri, Ulyan; Hady, Rosli (Jurnal Ilmiah Profesi Pendidikan, 2025)
This article examines a value-oriented approach to Arabic language education through the interpretive lens of the Qur’anic phrase Labanan Khalishan (pure milk), found in Surah an-Nahl (16): 66. The phrase is explored not only for its linguistic richness but also for its moral and symbolic implications, making it a meaningful medium for reinforcing both semantic understanding and character development in Arabic language learning. Employing a qualitative method and thematic textual analysis, this study delves into classical tafsir sources, contemporary linguistic commentaries, and educational perspectives. The integration of Labanan Khalishan as a pedagogical model highlights the convergence of semantic clarity (dalalah ma’na) and ethical values (akhlaqiyyah) in the educational process. The findings demonstrate that Quranic expressions, when contextualized in Arabic language education, can serve as powerful instruments for cultivating not only language competence but also spiritual and moral sensibilities. The article concludes that teaching Arabic through value-laden Qur’anic content fosters a more holistic, reflective, and character-centered language learning experience.